(untitled) (KYAMC Journal, 2013)
Chronic kidney disease is a worldwide public health problem with an increasing incidence and prevalence. Outcomes of chronic kidney disease include not only complications of decreased kidney function and cardiovascular disease but also end stage renal failure causing increased morbidity and mortality. The development of acute but serious uremic complications in advanced kidney disease may put the patient’s life at risk requiring immediate dialysis. The objective of this study was to find out the outcomes of urgent hemodialysis in advanced kidney disease, the minimum number of hemodialysis required for satisfactory clinical improvement, and to detect uremic emergencies associated with those patients. Twenty two patients with end stage renal failure admitted in a rural tertiary care private hospital of Bangladesh for emergency and short term dialysis were included in this study. For each patient hemodialysis was done at one day interval three times in a week in a dialysis unit. Results show that two sessions of hemodialysis produced 72 % and three sessions, almost 100% clinical recovery at satisfactory level. Urgent hemodialysis was found to be life saving in observed uremic emergencies like acute pulmonary edema, cerebral encephalopathy, metabolic acidosis, hyperkalemia, gross fluid overload and pericardial effusion. Dialysis therapy ameliorates many of the clinical manifestations of renal failure and postpones otherwise imminent death and for these logical reasons it is recommended that dialysis should not be delayed in uremic emergencies for the best interest of clinical outcomes. KYAMC Journal Vol. 3, No.-2, January 2013, Page 277-281 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15167